TAKSASI PRODUKSI TANAMAN KOPI DENGAN METODE ABC - Junaedi Junaedi; Sandi Syam; Syifa Al Mar'ah; Syahruni Thamrin; Muhammad Syafaat (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2020)
This study aims to determine the estimation results of coffee plant production at PT. Sulotco Jaya Abadi. The estimation activity is carried out using the ABC method, which is one of the main methods used at PT Sulotco Jaya Abadi. This method uses a random sample of land divided into 4 plots covering three criteria for fruit in the land, namely dense fruit, medium fruit, and low fruit, so that in this taxation each hectare uses 12 sample trees. The observations show that the estimated production value obtained at the coffee plantation at PT Sulotco Jaya Abadi is 1,393 kg per hectare. This value is in the range of the company's actual production for the last five years (2014-2018), namely 671 kg/ha to 2,638 kg/ha. The results of the estimation itself show an increasing trend in results in the last three years. Some of the things that are thought to have an effect on the calculated value obtained are the current plantation management as well as the skills / skills of the assessor when carrying out activities on the land which cannot be ignored. At the same time, the production value of 1,393 kg/ha can be used to plan the labor requirements for coffee pickers, which is 15 people per hectare with an estimated budget or harvest cost per hectare of IDR 1,393,000.